A New Computer Vision Approach for Active Pantograph Control - Aydin, Ilhan; Karakose, Ebru; Karakose, Mehmet; Gencoglu, M. Tunay; Akin, Erhan (Ieee, 2013)
Railway vehicles have become a modern transport media day by day. With the development of high-speed trains, this transportation way has been widely used for the transportation of people and cargo. However, several fault type in the pantograph-catenary system affects the performance of the train. Contact between a pantograph and catenary must slide along train movement. A sufficient lifting force should be applied to the contact wire when train moves. Vibrations occurred between a pantograph and catenary system and oscillations of contact wire cause the loss of contact. So, burst of arcing occurs in contact point. In this study, a new computer vision based method is proposed to control the contact force. The proposed algorithm utilizes the edge detection and Hough transform for detection of pantograph height. The obtained height is given to the control algorithm and the height of the pantograph is adjusted. The proposed method is verified by using a video taken from real pantograph and efficient results has been obtained.
IEEE International Symposium on INnovations in Intelligent SysTems and Applications (INISTA) -- JUN 19-21, 2013 -- BULGARIA
Keywords: pantograph; catenary; canny edge detection; hough transform; railways